Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle - Beaudouin, Célia; Suc, Jean-Pierre; Acherki, Nabila; Courtois, Laurent; Rabineau, Marina; Aloïsi, Jean-Claude; Sierro, Fransisco Javier; Oberlin, Christine (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.
Keywords: late quaternary; nw mediterranean sea; palynology

Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle - Beaudouin, Célia; Suc, Jean-Pierre; Acherki, Nabila; Courtois, Laurent; Rabineau, Marina; Aloïsi, Jean-Claude; Sierro, Fransisco Javier; Oberlin, Christine (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.
Keywords: late quaternary; nw mediterranean sea; palynology

A high resolution record of the last deglaciation in the southern Tyrrhenian Sea: environmental and climatic evolution - Buccheri, G.; Capretto, G.; Di Donato, V.; Esposito, P.; Ferruzza, G.; Pescatore, T.; Russo Ermolli, E.; Senatore, M. R.; Sprovieri, M.; Bertoldo, M.; Carella, D.; Madonia, G. (Marine Geology, 2002)
A multidisciplinary study was carried out on core C106 collected in the Salerno Gulf (southern Tyrrhenian Sea). Two tephra layers recovered in the core, δ18O record of Globigerinoides ruber and Globigerina bulloides and seven 14C calibrated ages provided the stratigraphic framework. The core sediments cover the last 28 kyr BP. Seismo-stratigraphic analysis of a high resolution acoustic profile, integrated by the dated core samples, allowed us to reconstruct the architecture and age of sedimentary bodies on the continental shelf. An integrated study based on different taxonomic groups (nannofossils, pteropods, foraminifera, and palynomorphs) provided palaeoclimatic trends, in agreement with changes in the isotopic composition of oxygen. The upper part of the Last Glacial period, the deglaciation phase and the Holocene were identified. Correlation between marine and continental records of palaeoenvironmental changes confirms a similar reconstruction of the last deglaciation as in the central and southern Mediterranean Sea. The Late Pleistocene–Holocene boundary was recognised at about 11.7 kyr BP. Between about 9.5 and 6 kyr BP and at 3.3 kyr BP some warmer episodes were recorded. The measured lower isotopic values, together with some features of the fossil assemblages recorded from 9.5 to 6 kyr BP, may be related to the oceanographic setting that led to the deposition of Sapropel S1 in the Mediterranean basin.
Keywords: isotopes; late quaternary; palaeoclimatology; sedimentology; seismic stratigraphy; Tyrrhenian Sea